Spinal Hamartoma in a Neonate: Unusual Presentation and MR Imaging Findings - Bining, H.J.S.; Saigal, G.; Goswami, R.S.; Gill, D.; McNeely, P.D. (American Journal of Neuroradiology, 2006)
SUMMARY: We report an extremely rare case of a congenital spinal cord hamartoma in a male neonate who presented with upper extremity weakness and a port wine stain on the right upper extremity and chest. MR imaging findings are described, and the importance of localizing the lesion in the spinal canal with respect to the dura and its impact on neurosurgical management is stressed.